The dawn of organic electronics. - Forrest, S.
Organic semiconductors are poised to transform the world of circuit and display technology. Major electronics firms such as Philips and Pioneer, and smaller companies such as Cambridge Display Technology, Universal Display, and Uniax, are betting that the future holds tremendous opportunity for the low cost and sometimes surprisingly high performance offered by organic electronic and optoelectronic devices. Using organic light-emitting devices (OLEDs), organic full-color displays may eventually replace liquid-crystal displays (LCDs) for use with laptop and even desktop computers. Such displays can be deposited on flexible plastic foils, eliminating the fragile and heavy glass substrates used in LCDs, and can emit bright light without the pronounced directionality inherent in LCD viewing, all with efficiencies higher than can be obtained with incandescent light bulbs
Keywords: Cambridge Display Technology; Philips; Pioneer; Uniax; Universal Display; Circuit technology; Desktop computers; Display technology; Flexible plastic foils; Laptop computers; Organic electronic devices; Organic electronics; Organic full-color displays; Organic light-emitting devices; Organic optoelectronic devices; Organic semiconductors